The Impact of National Cultures on Professional Values - Renqvist, Johanna (My University, 2012)
Cultural management and cross-cultural management are topical subjects in the global world of today. It is rather obvious that it is important to be aware of cultural differences when cooperating across borders, but most of the investigations and studies are only concerned with cultures that are very different. Cultures that are very similar in a global perspective can also be very interesting to investigate, because it is a bit more challenging when the differences are not too obvious. This fact, in combination with the regularly published PISA-results, which show that Finnish schools are managing far better than Swedish ditto, led to the research problem of this thesis. The aim of this study is to find out how national culture affects the (professional) values of public managers. In this case the public managers are headmasters in comprehensive schools in the Swedish-speaking parts of Finland and in Sweden. The purpose is to find out which values the headmasters hold, how the values held in Finland differ from those held in Sweden and if the different values, hence, the different cultures affect the management styles of the headmasters. This is a quantitative research carried out in the form of an electronic questionnaire answered by headmasters in the two countries. The questionnaire is based on theoretical studies central for this thesis, like the studies carried out by Hofstede, Schwarz and Rokeach. In addition to these theoretical studies, a wide range of books and articles are used in the study in order to be able to draw as proper conclusions as possible. The central findings of this study is that Finnish and Swedish headmasters have very similar values, but that it is possible to find some differences. It is remarkable that both Finnish and Swedish headmasters hold very benevolent values and they do not care too much about hedonism and tradition. However, the differences between the values held in Finland and the values held in Sweden lead to the fact that the cultural dimensions in the two countries ought to be slightly different. The conclusion of this thesis is thereby that the different values of the headmasters lead to different management style. Finnish headmasters practice a more employee-oriented management style, while Swedish headmasters are more taskoriented. The results of the study were somewhat surprising and did not really confirm the stereotypical view of Swedes and Finns.
Keywords: national culture; management style; values; headmasters; fi=Julkisjohtaminen: European Civil Servants - kansainvälisen hallinnon ohjelma|en=Public Management: European Civil Servants|